An analysis of the absorption rate of EU funded social projects at macro-regional level - Stan, Mari-Isabella; Cojocaru, Simona-Elena (Technium Social Sciences Journal, 2022)
The current European context is still characterized by the disparities between the Member States, economic and social cohesion being one of the priorities of the European Union, which is found among the key objectives of European and national policies. The Structural Funds are the most important economic policy measure adopted by the European Commission, and their management, which represents an opportunity for socio-economic development, is the responsibility of all Member States. In the national context, the responsibility for a sustainable local development must be placed on the community, one of the most effective tools for achieving the community’s development being social programs, implemented through social projects. The aim of this paper is to carry out an analysis of the projects contracted under the Human Capital Operational Programme, Priority Axis 4 - Social inclusion and combating poverty, for the 2014-2020 programming period, at the level of Romania’s development regions. For our country, the European Structural Funds are the main source of funding of the operational programmes which facilitate the socio-economic development at national, regional and local level, based on the premise that the development of social projects can lead to improved living conditions for the citizens of local communities.